A Review on Oral Liquid as an Emerging Technology in Controlled Drug Delivery System - Torne, Sangmesh R.; Sheela, Angappan; Sarada, N.C. (Current Pharmaceutical Design, 2018)
Background: The Oral Liquid Drug Delivery System (OLDDS) remains the primary choice of dosage form, though challenging, for the pharmaceutical scientists. In the last two decades, Oral Liquid Controlled Release (OLCR) formulation has gained a lot of attention because of its advantages over the conventional dosage forms. Method: The world of nanotechnology has paved multiple ways to administer the drug through oral cavity in liquid dosage form with an additional advantage of control over the release. In the current study, the various approaches towards the same have been discussed comprehensively to understand the different mechanisms of OLCR. Conclusion: This review also emphasizes on the existing techniques and the developments that have been made to improve on its efficacy including various formulation related factors. It also provides valuable insights into the role of polymers in the development of OLCR formulation that can be used in the management of Gastroesophageal Reflux Disease (GERD).
Keywords: alginate